Keadilan dalam Pendistribusian Royalti Hak Cipta Lagu dan Musik bagi Musisi: Analisis Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Sri Kurniati Handayani Pane (UIN Jakarta, 2026)
Abstract: Globalization and advancements in information technology have created new challenges in the protection of Intellectual Property (IP), particularly copyright in songs and musical works. The transformation of copyright into an economic asset has positioned royalties as the primary mechanism for distributing economic benefits to creators. However, the practice of royalty distribution in Indonesia continues to face structural issues, including the lack of clarity regarding royalty allocation between songwriters and performing musicians, which has led some creators to prohibit the use of their works. This study aims to examine the legal framework governing royalty distribution under Law Number 28 of 2014 concerning Copyright and to identify the factors influencing the prohibition of song usage by creators. The research employs a normative juridical method using statutory and conceptual approaches, analyzed through the theories of justice developed by John Rawls and Gustav Radbruch. The findings indicate that although legal protection has been normatively established, its implementation has yet to reflect substantive justice. Weak transparency in the royalty distribution system and the unequal bargaining position of creators constitute the primary factors contributing to disputes and restrictions on song utilization. This study recommends reforming the royalty management system to ensure greater fairness, transparency, and accountability in protecting the economic rights of creators effectively. Keywords: Royalties; Music Copyright; Distributive Justice; Copyright Law; National Collective Management Institute (LMKN).